Inhibition of candida albicans biofilm using topical antifungal creams / Alya Nur Athirah Kamaruzzaman - Kamaruzzaman, Alya Nur Athirah (2022)
Candida albicans is a microbial fungus that exists as a commensal member of the human microbiome and an opportunistic pathogen. Biofilm formation by this fungal pathogen occurs mostly in the mucosa or endothelium associated with candidiasis and also colonizes medical devices, such as vascular and urinary catheters and dentures. Improper use of antifungal agents has caused drug resistance. It happened when there are too many antifungal drugs used to treat diseases caused by C. albicans. The aim of this research was to determine the effects of the antifungal creams on biomass, viability and biochemical composition of C. albicans biofilm. Four commercial antifungal creams were selected herein namely econazole nitrate (Cream A), miconazole nitrate (Cream B), ketoconazole (Cream C) and tolnaftate (Cream D) -based antifungal creams. Crystal violet assay, resazurin assay and infrared spectral analysis were performed to determine the biomass, viability and biochemical composition of C. albicans biofilm respectively. Among these four antifungal creams, miconazole nitrate-based antifungal cream (Cream B) showed the strongest inhibition of biofilm biomass (65.12%) and viability (17.08%). Miconazole nitrate-based antifungal cream showed that nucleic acid was affected through the shifting of Fourier transform infrared (FTIR) spectra at a wavenumber of 1240 cm-1. The findings from the present study may be useful to control disease caused by C. albicans such as candisiasis which had been categorised as a main problem affected on human being.